POTRET PEMAKAIAN BAHASA PADA RUANG PUBLIK DI KABUPATEN BENGKULU UTARA (The Potrait of Language Use in Public Places in Bengkulu Utara Regency) - Syamsurizal Syamsurizal (SALINGKA, 2017)
Indonesian language is the most popular among languages in archipilago. Because of that it is natural the use of that language has a huge attention from its user. This article aims at describing, indicating deviated forms, and knowing their causes of Indonesian use in public places in Bengkulu Utara Regency. The method of the study is qualitative and the data taken from the name of the building, road, housing, institution, public facility, advertisement, etc. The result of the study shows that the use language in public places divided into six types, such as Indonesia Language, Indonesia in Kaganga letters, English, combination of Indonesia and English, Indonesia and Java, and Indonesia and Sanskirt. The deviation of Indonesia use covered spelling and diction. Spelling deviation covers the mistake of letters writing,punctuation, and words. It is caused by purposed and unpurposed acts.